The business of politics: Sun TV and the Maran brothers - Guha Thakurta, Paranjoy (2015)
A heady cocktail of politics, business emerges from the developments relating to one of India's biggest media conglomerates, the Chennai-based Sun group. The actions of different wings of the union government against Sun's owners, the politically influential Maran brothers, have raised a number of questions relating to allegations of breaking rules, taking advantage of proximity to power, economic offences and freedom of expression. These issues have, in turn, become embroiled in factional politics within the ruling Bharatiya Janata Party in New Delhi and in the Dravida Munnetra Kazhagam in Chennai, which is currently out of power both in the centre and in Tamil Nadu. - Reproduced.
Keywords: Crime